2020
DOI: 10.3390/ijms21114077
|View full text |Cite
|
Sign up to set email alerts
|

Reg3α and Reg3β Expressions Followed by JAK2/STAT3 Activation Play a Pivotal Role in the Acceleration of Liver Hypertrophy in a Rat ALPPS Model

Abstract: To explore the underlying mechanism of rapid liver hypertrophy by liver partition in associating liver partition and portal vein ligation for staged hepatectomy (ALPPS), liver partition at different sites was investigated. Increased inflammatory cytokines owing to the liver partition have been reportedly responsible. If this were true, rapid liver hypertrophy should be achieved regardless of where the liver was split. A male Sprague-Dawley rat model was created, in which a liver split was placed inside the por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Upon binding, Fgfr4 can signal mitosis independently of Foxm1b via mitogen activated protein kinases (MAPK) and via the nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-κB). Activation of the Stat3 pathway by Fgf15 binding to Fgfr4 [ 42 ] has been observed following ALPPS [ 43 , 44 ], but did not play a role in our model given the downregulation of Foxm1b , a downstream target of Stat3 [ 8 ]. Alternatively, BAs can bind to the nuclear receptor pregnane X receptor (PXR) and trigger mitosis while bypassing Stat3 and Foxm1b.…”
Section: Discussionmentioning
confidence: 97%
“…Upon binding, Fgfr4 can signal mitosis independently of Foxm1b via mitogen activated protein kinases (MAPK) and via the nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-κB). Activation of the Stat3 pathway by Fgf15 binding to Fgfr4 [ 42 ] has been observed following ALPPS [ 43 , 44 ], but did not play a role in our model given the downregulation of Foxm1b , a downstream target of Stat3 [ 8 ]. Alternatively, BAs can bind to the nuclear receptor pregnane X receptor (PXR) and trigger mitosis while bypassing Stat3 and Foxm1b.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study has demonstrated that the expression of PCNA is about ten-fold higher in rats after ALPPS compared with the transection and left lateral lobe resection groups, and four-fold higher compared with the PVL group (24). Intriguingly, both Borger et al and Otsuka et al proposed that there may be other signaling pathways involved in the accelerated liver regeneration after ALPPS (25,26). Therefore, this current study performed bioinformatics analyses to screen the differentially expressed genes before and after ALPPS and PVL in rats.…”
Section: Discussionmentioning
confidence: 98%
“…Type I (and Type II) Reg proteins are expressed in regenerating islets [ 39 , 52 ] and involved in β-cell regeneration [ 3 , 40 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. It has been suggested that Reg family proteins are involved in cellular proliferation in exocrine pancreatic cells [ 62 , 63 ], gastrointestinal cells [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], hepatic cells [ 76 , 77 , 78 , 79 , 80 ], salivary ductal cells [ 81 , 82 , 83 ], bone and muscle cells [ 84 , 85 ], neuronal cells [ 86 ], and cardiovascular cells [ 30 , 32 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%